GG Carinae: Discovery of orbital phase dependent 1.583-day periodicities in the B[e] supergiant binary - Porter, A; Blundell, K; Podsiadlowski, P; lee, S (Oxford University Press, 2021)
GG Carinae (GG Car) is a binary whose primary component is a B[e] supergiant. Using photometric data from the Transiting Exoplanet Survey Satellite (TESS), All Sky Automated Survey (ASAS), Optical Monitoring Camera (OMC), and All Sky Automated Survey for Supernovae (ASAS-SN), and spectroscopic data from the Global Jet Watch to study visible He I, Fe II, and Si II emission lines, we investigate the short-period variations that are exhibited in GG Car. We find a hitherto neglected periodicity of 1.583156 ± 0.0002 d that is present in both its photometry and the radial velocities of its emission lines, alongside variability at the well-established ∼31-d orbital period. We find that the amplitudes of the shorter period variations in both photometry and some of the emission lines are modulated by the orbital phase of the binary, such that the short-period variations have largest amplitudes when the binary is at periastron. There are no significant changes in the phases of the short-period variations over the orbital period. We investigate potential causes of the 1.583-d variability, and find that the observed period agrees well with the expected period of the l = 2 f-mode of the primary given its mass and radius. We propose that the primary is periodically pulled out of hydrostatic equilibrium by the quadrupolar tidal forces when the components are near periastron in the binary’s eccentric orbit (e = 0.5) and the primary almost fills its Roche lobe. This causes an oscillation at the l = 2 f-mode frequency that is damped as the distance between the components increases.